Phase II Study of Single-Agent and Combination Everolimus and Panobinostat in Relapsed or Refractory Diffuse Large B-Cell Lymphoma. (26th November 2021) - Islam, Prioty; Rizzieri, David; Lin, Chenyu; de Castro, Carlos; Diehl, Louis; Li, Zhiguo; Moore, Joseph; Morris, Tod; Beaven, Anne
Abstract: Novel therapeutics are needed for patients with relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL). Everolimus is an mTOR pathway inhibitor with synergistic anti-tumor activity when combined with histone deacetylase inhibitors, such as panobinostat, in preclinical lymphoma models. In this Phase II study, we evaluated overall response rate to single and combination everolimus and panobinostat in R/R DLBCL. Fifteen patients were enrolled to single-agent and 18 to combination. One patient responded to everolimus, while none responded to panobinostat. Though 25% of patients responded to combination therapy, responses were not durable with significant toxicity. We demonstrated minimal single-agent activity and prohibitive toxicity with combination therapy.